DAMPAK ALIH FUNGSI LAHAN SAWAH TERHADAP PRODUKSI PADI DAN PENDAPATAN PETANI DI KOTA GORONTALO - Botutihe, Abdul Rais; Olilingo, Fachrudin Zain; Mopangga, Herwin (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
Gorontalo City as the provincial capital has unique economic characteristics. This city has broader government, economic, and cultural functions compared to Gorontalo Regency and Bone Bolango Regency. However, this also causes greater economic pressure, so that many rice fields are converted into non-agricultural land. This study aims to determine the factors that influence land conversion, to determine the impact of rice field conversion on rice production in Gorontalo City and to determine the impact of rice field conversion on farmer income in Gorontalo City. The results of the study indicate that instead of land function being driven by economic pressure, high land price offers, minimal support for the agricultural sector, the need for housing development, commercial development, and infrastructure. The impacts include a decrease in the area of ​​rice fields, which causes a significant decrease in rice production. In addition, farmers experience a decrease in income from the agricultural sector, so that many have to rely on non-agricultural sources of income.